Effect of Acupotomy Therapy on Lateral Epicondylitis Diagnosed by Ultrasonography - Lim Nara; Lim Jinyoung; Kim Dongwoung; Lee Jongdeok; Kim Sungchul (Korean Pharmacopuncture Institute, 2011)
Purpose: This observation was to report the clinical effects of acupotomy in treating lateral epicondylitis. Methods: Three patients diagnosed with lateral epicondylitis were treated with acupotomy. Two were male and one was female. The improvement of symptom were evaluated by visual analog scale (VAS) and self-consciousness symptoms of Cozen test. Results: After one treatments, patient's chief complaint and the pain near the lateral epicondyle while cozen test were notably improved. Conclusions: This study demonstrates that oriental medical treatment with acuputomy therapy has significant effect in improving symptoms of lateral epicondylitis. As though we had not wide experienced in this treatment, more research is needed.